Autoimmune gastritis: comorbid pathology in type 1 diabetes - Olga S. Derevyanko; Liudmila I. Ibragimova; Magomedkerim R. Ragimov; Tatiana V. Nikonova (Сахарный диабет)
In recent years noted an increased number of patients with autoimmune diseases (AID), and the special attention deserves combination of several autoimmune pathologies collected in one patient, because such patients requires special tactics of management. Autoimmune diseases of the gastrointestinal tract are less researched and, nevertheless, prognostically unfavorable. Autoimmune gastritis (AIG) has a special place in other stomach diseases, which develops in the aggregate with type 1 diabetes. AIG is a chronic inflammation of the mucous membrane of the body of the stomach, leading to the appearance of atrophy and hypoxecretion. AIG is found in 5–10% of individuals in general population, with a higher incidence of AIG in patients with diabetes and other established autoimmune pathology. AIG is asymptomatic at the early stage of the disease and clinical manifestations appear after the atrophic changes in the mucous membrane of the stomach develop. Since autoimmune gastritis does not have pathognomonic signs, it can manifest itself in hematological and oncological complications at later stages. This is why screening, early diagnosis, prevention and treatment are very important. Early diagnosis and prevention of AIG and its complications play the main role. This article provides an overview of the worldwide data dedicated to this issue.